مساهمات الإمام أحمد عبد الرحمن البنا الساعاتي في الدراسات القرآن والحديث النبوي - Nunun Zainun binti Ahmad Hidayat (Universitas Darussalam Gontor, 2014)
Al-Imam al-Banna al-Sa‘ati (d.1378AH/1958CE) was amongst the famous Egyptian scholars in the 14th century. Although mostly known as the father to the late Hasan al-Banna, he was also a prolific scholar in his own right. In the field of hadith and its studies, he has composed important works such as al-Fath al-Rabbani fi Tartib Musnad Ahmad ibn Hanbal al-Syaibani, Bada’i‘ al-Minan fi Jam‘ wa Tartib Musnad al Syafi‘i wa al-Sunan, and others. In addition, he was also the first amongst scholars to have successfully organized the hadiths of Musnad Ahmad into thematic chapters to facilitate the finding of hadith in the book. However, his scholarly contributions have yet to attract the interest of the researchers as their subject of study. Therefore, this paper aims to expound on this matter in a greater detail. In particular, its aims to highlight the little known biography of this scholar as well as his contributions to the field of al-Qur’an and al-Hadith and its sciences. The study employs the historical, deductive and analytical approaches in analyzing the relevant sources on the matter. It is hoped that the paper provides an important aspect of hadith scholarship as portrayed by this important scholar.